2012
DOI: 10.1371/journal.pone.0045374
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nanovesicles Formed by the Self-Assembly of Branched Amphiphilic Peptides

Abstract: Peptide-based packaging systems show great potential as safer drug delivery systems. They overcome problems associated with lipid-based or viral delivery systems, vis-a-vis stability, specificity, inflammation, antigenicity, and tune-ability. Here, we describe a set of 15 & 23-residue branched, amphiphilic peptides that mimic phosphoglycerides in molecular architecture. These peptides undergo supramolecular self-assembly and form solvent-filled, bilayer delimited spheres with 50–200 nm diameters as confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
146
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(150 citation statements)
references
References 42 publications
1
146
0
Order By: Relevance
“…In addition to the previous sequence, the amphiphilic peptide sequence was obtained with C-terminus attachment of two hydrophobic adhesive sequences, FLIVIGSII and FLIVI, in a parallel array into branched structures with predetermined amino acids, resulting in self-assembly towards solvent-filled bilayered vesicles with 50–200 nm range [110] (Figure 4). The in vitro studies showed the cellular uptake of vesicles, their accumulation within the perinuclear space membrane, and their potential for encapsulating larger molecules such as hydrophilic drugs, peptides, proteins and large plasmids [110].…”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the previous sequence, the amphiphilic peptide sequence was obtained with C-terminus attachment of two hydrophobic adhesive sequences, FLIVIGSII and FLIVI, in a parallel array into branched structures with predetermined amino acids, resulting in self-assembly towards solvent-filled bilayered vesicles with 50–200 nm range [110] (Figure 4). The in vitro studies showed the cellular uptake of vesicles, their accumulation within the perinuclear space membrane, and their potential for encapsulating larger molecules such as hydrophilic drugs, peptides, proteins and large plasmids [110].…”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…The in vitro studies showed the cellular uptake of vesicles, their accumulation within the perinuclear space membrane, and their potential for encapsulating larger molecules such as hydrophilic drugs, peptides, proteins and large plasmids [110]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…After de-protection of the side chain amino group of the lysine using 80% TFA in dichloromethane chloride (DCM); the N-Hydroxysuccinimide ester of the 5/6-carboxy-tetramethyl rhodamine was used to couple the dye to the ε-amino site of a lysine residue in the presence of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 7 N,N-Diisopropylethylamine (DIEA). The remainder of the synthesis was carried out as previously detailed 22 .…”
Section: Peptide Synthesismentioning
confidence: 99%
“…Recently, we reported results on a set of peptides that self-assemble to form stable nanocapsules 22 with lipid-like properties 23 . The Branched Amphiphilic Peptides Capsules, termed BAPCs are able to encapsulate, retain and deliver (in vitro) a variety of solutes into cells, including the alpha-emitting 225 Actinium and its radioactive daughter radionuclides 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic peptides that tend to adopt the b-sheet structure have been shown to assemble into various nanoscale morphologies, such as fibrils, nanotubes and liposomes. [9][10][11] Amphiphilic peptides can also be directed to form hydrogels composed of elongated fibril assemblies with widths in the nanometer range. 1,7,8,12 These self-assembled peptide matrices have been shown to function as drug delivery systems and as scaffolds that mimic extracellular matrices, useful for tissue regeneration purposes.…”
Section: Introductionmentioning
confidence: 99%